THE INFLUENCE OF MASS MEDIA REPORTING ON THE RESCUE AND FORMULATION OF ENVIRONMENTAL LAWS IN KEDIRI - Zainal Arifin; Emi Puasa Handayani (Universitas Muhammadiyah Ponorogo, 2022)
News coverage by the mass media is very influential on the way of thinking and behaving society in saving the environment from damage. Examples are pollution, abuse of natural resources and environmental protection. Media coverage also influences policy makers in formulating environmental law policies. Aspects of communication and policy aspects have interrelationships that affect each other. In the empirical level the relationship is reflected in the public perception when responding to environmental problems. The mass media as a social institution has contributed to the worldview and thinking of the community and policy makers. This study focuses on the interrelation or relationship between press coverage with rescue and environmental law formulation policy. The purpose of research to determine the influence of mass media coverage on rescue and environmental management policy. This type of research is qualitative research with mass media content analysis method combined with in-depth interview technique to source and stake holder applied in this research. Data processing is done by manual coding technique, coding sheet and interview guide. The analysis is done by qualitative and quantitative descriptive approach presented in the form of frequency table and bar diagram. Interview results are used to sharpen the analysis. The result, that the continuous and continuous mass media coverage and deep, was able to stop environmental destruction, especially illegal sand mining in the Brantas River Basin of Kediri. Second, the government in taking environmental law policy is influenced by mass media coverage. The conclusion of this research is that the mass media influence the cessation of illegal sand mining activity in Brantas River Basin of Kediri. Both media coverage influenced policy makers to formulate legal policy in Kediri.